DISCURSO METALINGÜÍSTICO NA AULA DE DUAS PROFESSORAS DE LÍNGUA INGLESA - Almeida, Márcia Cristina Fontes; Dutra, Deise Prina (Intercâmbio, 2010)
The objective of this work is to describe how two teachers use grammatical terminology in English as foreign language classes, to understand the teachers’ reasons to use or to avoid metalanguage, and to identify what influenced their behavior. The results reveal that grammar teaching is present in both English classes observed. The difference was on the use or avoidance of the grammatical terms. The teachers' actions were based on cognitive, contextual and experiential factors. The factor that influenced most their classroom decisions was their experiences as L1 and FL students.